Differentiation of Cancer Stem Cells by Using Synthetic Small Molecules: Toward New Therapeutic Strategies against Therapy Resistance. (16th September 2020) - Maucort, Chloé; Di Giorgio, Audrey; Azoulay, Stéphane; Duca, Maria
Abstract: Despite the existing arsenal of anti‐cancer drugs, 10 million people die each year worldwide due to cancers; this highlights the need to discover new therapies based on innovative modes of action against these pathologies. Current chemotherapies are based on the use of cytotoxic agents, targeted drugs, monoclonal antibodies or immunotherapies that are able to reduce or stop the proliferation of cancer cells. However, tumor eradication is often hampered by the presence of resistant cells called cancer stem‐like cells or cancer stem cells (CSCs). Several strategies have been proposed to specifically target CSCs such as the use of CSC‐specific antibodies, small molecules able to target CSC signaling pathways or drugs able to induce CSC differentiation rendering them sensitive to classical chemotherapy. These latter compounds are the focus of the present review, which aims to report recent advances in anticancer‐differentiation strategies. This therapeutic approach was shown to be particularly promising for eradicating tumors in which CSCs are the main reason for therapeutic failure. This general view of the chemistry and mechanism of action of compounds inducing the differentiation of CSCs could be particularly useful for a broad range of researchers working in the field of anticancer therapies as the combination of compounds that induce differentiation with classical chemotherapy could represent a successful approach for future therapeutic applications. Abstract : Oncogenic zugzwang : Cancer stem cells (CSCs) are a main reason for therapeutic failure in a number of different tumors. Herein, we review current small‐molecule drugs that can induce differentiation of CSCs toward cancer cells that are sensitive to chemotherapy. Combining such compounds with chemotherapy could lead to tumor eradication thus representing a promising approach for future therapies.